MEASUREMENT OF THE DETERIORATION OF THE DIESEL ENGINE OIL USING THE IDT CAPACITOR SENSOR - Lee, Sang Hoon; Cho, Youn Joung; Sin, Tae Ho; Jeon, Jae Hyeon (International Journal of Research -GRANTHAALAYAH, 2022)
A capacitor-type engine oil sensor is designed and fabricated to measure the property of the diesel engine oil depending on the vehicle mileage. This sensor has flat structure with the interdigitated (IDT) electrodes for the smooth oil flow and is constructed using printed circuit board (PCB) for the fabrication convenience. For the increased capacitance, the smaller spacing between the electrodes is preferred and determined with 0.5 mm based on the fabrication limit. The device is applied to actual trucks with diesel engine. From the experiment, the capacitance of vehicle A is initially constant and then increased upto approximately 6,000 km. And then, the output is dramatically decreased, which indicates that the engine oil has been degraded and should be replaced. The interval at which the reduction in capacitance occurs varies depending on each vehicle, which means the exchange interval of engine oil is different from each other. The degree of deterioration of the oil is also measured with the viscosity tests and total acid number (TAN) tests, and the results are compatible with the measurement of capacitance. From these results, it has been confirmed that the fabricated IDT capacitor sensor can measure the engine oil conditions depending on the mileage.